(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
The rapid expansion of corporate sustainability reporting has increased transparency requirements while raising concerns about greenwashing—the practice of making misleading environmental claims. Traditional ESG auditing, often termed "ESG 1.0," relies on lagged, self-reported data that is prone to selective disclosure. This article introduces the ESG 2.0 paradigm, where Artificial Intelligence (AI) acts as an independent auditor. By fusing Natural Language Processing (NLP) and Geospatial Intelligence, stakeholders can now quantify "The Credibility Gap" between corporate narratives and physical reality.